Long-term use of rituximab increases T cell count in MS patients - Björnsson, Gunnar Sigfús; Sigurgrímsdóttir, Hildur; Maggadóttir, Sólrún Melkorka; Einarsdóttir, Berglind Ósk; Sveinsson, Ólafur Árni; Hjaltason, Haukur; Sigurðardóttir, Sigurveig Þóra; Lúðvíksson, Björn Rúnar; Brynjólfsson, Siggeir Fannar (Frontiers in Immunology, 2024)
Rituximab has been used to treat MS patients in Iceland for over a decade. However, long-term effect of rituximab on leukocyte populations has not yet been elucidated. By retrospective analysis of flow cytometric data from 349 patients visiting the neurological ward at The National University Hospital of Iceland from 2012 to 2023 for rituximab treatment, the long-term effect of rituximab and whether the effect was dose dependent (1000mg vs 500mg) was evaluated. No difference was detected in efficacy of B cell depletion in patients treated with 500mg as an initial dose of rituximab when compared to 1000mg. Long-term use of rituximab led to an increase in T cell count (p=0,0015) in patients receiving 3-8 doses of rituximab (1.5-8 years of treatment). The increase occurred in both CD4+ (p=0,0028) and CD8+ T cells (p=0,0015) and led to a decrease in the CD4/CD8 ratio (p=0,004). The most notable difference lies in reshaping the balance between näive and effector CD8+ T cells. The clinical implications of long-term treatment with rituximab and its effect on the T cell pool needs to be explored further. Since no difference in B cell depletion was detected between the two patient groups, 1000mg as an initial dose might be excessive, suggesting a personalized dosing regimen might have therapeutic and financial advantages.